2012
DOI: 10.1017/s0029665112000699
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between BMI and metabolomic profiles: a focus on amino acids

Abstract: The role of metabolomics in the field of nutrition is continuing to grow and it has the potential to assist in the understanding of metabolic regulation and explain how minor perturbations can have a multitude of biochemical endpoints. It is this development, which creates the potential to provide the knowledge necessary to facilitate a more targeted approach to nutrition. In recent years, there has been interest in applying metabolomics to examine alterations in the metabolic profile according to weight gain/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 30 publications
7
64
1
2
Order By: Relevance
“…Higher levels of circulating BCAAs have been reported in obese individuals compared to lean individuals [35,39], with a number of studies reporting a reduction in BCAAs levels after weight loss [26,28]. BCAAs predicted improvements in insulin resistance in patients participating in a weight loss intervention [31,49], and a positive association between BCAAs and insulin resistance has been also reported [34,49].…”
Section: Discusionmentioning
confidence: 99%
“…Higher levels of circulating BCAAs have been reported in obese individuals compared to lean individuals [35,39], with a number of studies reporting a reduction in BCAAs levels after weight loss [26,28]. BCAAs predicted improvements in insulin resistance in patients participating in a weight loss intervention [31,49], and a positive association between BCAAs and insulin resistance has been also reported [34,49].…”
Section: Discusionmentioning
confidence: 99%
“…in the study design and sample-collection procedureFactorRecommendationsMain metabolites and references (selected examples)Sex a Match the distribution of sexLipids [45, 46], orthophosphate, α-tocopherol, creatinine, DHEA-S [47], cholesterol [44]AgeMatch the distribution of ageAmino acids [48], isocitrate, succinate, malate, lactate, etc. [47]Body mass index (BMI)Refer to BMI before the enrollment of participants, and match for BMIBCAA [4951], lipids, steroids [52]Fasting and feeding12 h fasting (usually overnight)Essential amino acids and acylcarnitines [53], triglycerides and homocysteine [54]Circadian rhythmKeep normal biorhythm; collect samples at the same time point (usually in the morning); take circadian rhythm into account if metabolite concentrations follow a rhythmLipids [55], BCAA, lactate [56], bilirubin, cortisol [56, 57]Exercise; stressAvoid unaccustomed physical activity; avoid stress before drawing bloodLactate, free fatty acids, glucose, amino acids and acylcarnitines [53, 58], uric acid [44], creatinine and many othersDrugs and/or nutritional supplements (e.g. vitamins, amino acids)At least 12 h abstention, preferably 24 h or longer

a Sex-specific differences in metabolite concentrations should always be assumed until proved otherwise

…”
Section: Preparation Before Blood Collectionmentioning
confidence: 99%
“…Not by chance, milk provides highest amounts of leucine in comparison to all other animal proteins to optimise mTORC1 activation for postnatal growth. Several recent metabolomics studies underline the relationship between high plasma BCAA profiles, increased BMI and insulin resistance recently reviewed by Morris et al (18). Thus, acne appears to develop in a metabolic environment with increased mTORC1 signalling and has been proposed to represent a visible mTORC1-driven disease of civilisation (19).…”
Section: Mtorc1-activity and Body Mass Indexmentioning
confidence: 99%
“…First evidence supporting a correlation between milk consumption and BMI has been provided by the Growing Up Today Study (10 and pivotal activators of the amino acid-sensitive enzyme mTORC1, have been associated with obesity and future insulin resistance in children and adolescents in the United States (22). There is accumulating evidence that high plasma levels of BCAAs are associated with insulin resistance (18). In fact, Hoppe et al (23) have demonstrated that high intake of milk protein (53 g/ day), but not meat (53 g/day) increased basal insulin serum levels and induced insulin resistance in 8-yearold Danish boys.…”
Section: Milk and Increased Body Mass Indexmentioning
confidence: 99%